Normobaric hypoxia does not alter the critical environmental limits for thermal balance during exercise-heat stress - Coombs, G. B.; Cramer, M. N.; Ravanelli, N.; Imbeault, P.; Jay, O. (Experimental Physiology, 2021)
" What is the central question of this study? Hypoxia reportedly does not impair thermoregulation during exercise in compensable heat stress conditions, but whether it has an impact on maximal heat dissipation and therefore the critical environmental limit for the physiological compensability of core temperature is unknown. " What is the main finding and its importance? Although skin blood flow was higher in hypoxia, no differences in sweat rates or the critical environmental limit for the physiological compensability of core temperature - an indicator of maximal heat loss - were found compared to exercise in normoxia, indicating no influence of normobaric hypoxia on thermoregulatory capacity in warm conditions. Abstract Altered control of skin blood flow (SkBF) in hypoxia does not impair thermoregulation during exercise in compensable conditions, but its impact on maximal heat dissipation is unknown. This study therefore sought to determine whether maximum heat loss is altered by hypoxia during exercise in warm conditions. On separate days, eight males exercised for 90 min at a fixed heat production of appr. 500 W in normoxia (NORM) or normobaric hypoxia (HYP, FIO2 = 13%) in a 34 °C environment. Ambient vapour pressure was maintained at 2.13 kPa for 45 min, after which it was raised 0.11 kPa every 7.5 min. The critical ambient vapour pressure at which esophageal temperature inflected upward (Pcrit) indicated that maximum heat dissipation had been reached. Neither local sweat rates on the upper arm, back and forehead [average NORM: 1.46 (0.15) vs. HYP: 1.41 (0.16) mg cm-2 min-1; P = 0.59] nor whole-body sweat losses [NORM: 1029 (137) g vs. HYP: 1025 (150) g; P = 0.95] were different between trials. Laser-Doppler flux values (LDF; arbitrary units), an index of SkBF, were not different between NORM and HYP on the forearm (P = 0.23) or back (P = 0.73); however, when normalized as a percentage of maximum, LDF values tended to be higher in HYP compared to NORM at the forearm (condition effect, P = 0.05) but not back (P = 0.19). Despite potentially greater SkBF in hypoxia, there was no difference in Pcrit between conditions [NORM: 3.67 (0.35) kPa; HYP: 3.46 (0.39) kPa; P = 0.22). These findings suggest that hypoxia does not independently alter thermoregulatory capacity during exercise in warm conditions.